PECULIARITIES OF COMMUNICATION MANAGEMENT AT THE ENTERPRISE - Mykhaliuk , Н.; Binert , О.; Fedyk , О.; Syniuk , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
A modern enterprise is an extremely complex object of management. It is characterized by a complex nature, the need of accounting of economic, technical and political factors, complexity of both technical and organizational spheres of activity, close connection with the external environment and its components, etc. The problem of increasing the level of efficiency in the use of enterprise resources for the further market development is primarily related to the use of up-to-date and reliable information about the external and internal environment. The most important goal of internal communication in the organization is to create support for the goals and policy of the organization by employees. It is a properly built and effective communication system of the enterprise that can ensure fulfillment of tasks. When communicating, employees receive the necessary knowledge and motivation, become better defenders and promoters of the company's plans. Communication is a significant aspect of social interaction, and one of the most common features of any activity. Communication can be defined as a form of interaction, as one of the manifestations of information exchange or exchange of information between living beings in the process of their direct communication by using technical means. Well-established communication contributes to ensuring the organization efficiency. It is considered that if an organization is effective in the field of communication, it is effective in all other activities. Communication is one of the necessary conditions for a person to live in the society, and sociability is one of the important system characteristics associated with the success. It represents a new form of political, scientific, organizational and technical power in the society, which helps the organization to be included in the external environment, and there is an exchange of ideas or information to ensure mutual understanding. It has a rather broad explanation. Every process must be managed, especially such large and important process for each organization performance as flow of information in the process of its functioning. It is extremely important to manage the production process, the processes of supply and shipment of products, the process of hiring and training employees, etc. But all these processes cannot be managed without the organized flow of information.